Simulation of solar cell losses depending on cell design - Sols, Kajsa (My University, 2010)
Solarion AG manufacture thin film solar cells from CIGS absorber material. In an effort tomake the electricity production cheaper one approach is to optimise them, without increasing the production cost. In this project their cells were simulated with the finite element method. The layout and layer thicknesses of the front contact were considered as well as the back contact conductivity. It was concluded that the transparent conductive oxide in the front contact and the opaque, highly conductive grid printed on top, should be optimised to give a maximal efficiency. Further the cells could be adjusted to low illumination intensities by decreasing the grid coverage. Further, simulations of a highly resistive i-ZnO layer in the front contact indicate that; the layer can be used to stop short circuits between the front and back contact of the cell.
Keywords: Fysik; Physical Sciences